(3GdcJGHs - (3YeQh Hf YKeGf Hf bfHQ GdMGQKj, SjHhjg, CHh HTQ , J (B180 (3g` s
(3ChdgG (B:s
(3gPG HGH Yde eG Gdcde ef GdYQHjI s
(3BNQgG (B:s
(3BNQg eHJhQ , jfJgi Hbhdg (B: (3gPG HGH eG Med Ydi ehVY GdYGed ai GdGSe s
(3GdfSNI HgG MhGTs
(3GdfSNI ecJhHI HQSe GdabjI eYR GdOjf GdhTGM Hf Ydi Hf CHj HcQ Hf YHO cdGd GdMejQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B10s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdfMhs